Translation of Literary Language with Special Focus on Idioms - Abdulrazzaq, Dr Afif Othman (Manar Elsharq Journal for Literature and Language Studies, 2026)
This research addresses problems of translating literary language, i.e., of idioms, and figures of speech such as metaphors, similes, personifications, and alliterations with special focus on idioms from English into Arabic. Those problems result from many factors which can be objective, generic, and even affective factors. What is important here is the translator’s education background and experience in translating, first, then the affective factor which is the readers’ responses on the idiom’s translation quality, second. Through this evaluative qualitative research, it is found that idioms were translated by using idiomatic translation method while metaphors, similes, personifications, and alliterations were translated by using literal translation method. Idioms were translated accurately, whereas the translation of metaphors, similes, personifications, alliterations have not been very accurate. Based on the naturalness level, the translation of idioms is natural, while metaphors, similes, personifications, and alliterations are not yet natural.